2016
DOI: 10.1111/clr.12912
|View full text |Cite
|
Sign up to set email alerts
|

Experimental mucositis and experimental gingivitis in persons aged 70 or over. Clinical and biological responses

Abstract: ObjectivesTo compare in persons aged 70 years or older the clinical and inflammatory changes occurring around implants and natural teeth during and after a phase of undisturbed plaque accumulation.Material and methodsTwenty partially edentulous participants with titanium implants refrained from oral hygiene practices while being clinically monitored in weekly intervals for 21 days. Teeth and implants were then cleaned, oral hygiene resumed, and the participants were further monitored for 3 weeks. Twelve biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 36 publications
4
90
2
4
Order By: Relevance
“…This indicated that resolution of experimental peri‐implant mucositis in humans may take longer than 3 weeks (Table ). In contrast to the study by Salvi et al., all clinical parameters assessed in an elderly patient sample (i.e., ≥70 years) returned to pre‐experimental levels after 3 weeks of reinstituted biofilm control, thus documenting reversibility of experimentally induced peri‐implant mucositis …”
Section: Is Biofilm‐induced Peri‐implant Mucositis a Reversible Disease?contrasting
confidence: 78%
See 3 more Smart Citations
“…This indicated that resolution of experimental peri‐implant mucositis in humans may take longer than 3 weeks (Table ). In contrast to the study by Salvi et al., all clinical parameters assessed in an elderly patient sample (i.e., ≥70 years) returned to pre‐experimental levels after 3 weeks of reinstituted biofilm control, thus documenting reversibility of experimentally induced peri‐implant mucositis …”
Section: Is Biofilm‐induced Peri‐implant Mucositis a Reversible Disease?contrasting
confidence: 78%
“…Resolution of host biomarkers in peri‐implant crevicular fluid following 21 days of reinstituted biofilm control…”
Section: Definition Of Peri‐implant Mucositismentioning
confidence: 99%
See 2 more Smart Citations
“…Premature loading, tobacco smoking, and systemic conditions such as diabetes have been associated with early implant loss (De Bruyn & Collaert, 1994;Mombelli & Cionca, 2006). Clinical experiments (Meyer et al, 2017;Pontoriero et al, 1994;Salvi et al, 2012;Zitzmann, Berglundh, Marinello, & Lindhe, 2001) have established a causeeffect relationship between biofilm formation and inflammation, with a stronger clinical reaction around implants compared to teeth. Factors associated with peri-implantitis and late failures include periodontitis, smoking, and diabetes mellitus (Atieh, Alsabeeha, Faggion, & Duncan, 2013;Bornstein, Cionca, & Mombelli, 2009;Derks & Tomasi, 2015;Heitz-Mayfield & Huynh-Ba, 2009;Karoussis, Kotsovilis, & Fourmousis, 2007;Klokkevold & Han, 2007;Ong et al, 2008;Quirynen, Abarca, Van Assche, Nevins & van Steenberghe, 2007;Safii, Palmer, & Wilson, 2010;Schou, Holmstrup, Worthington, & Esposito, 2006;Stacchi et al, 2016).…”
Section: Biological Complications Of Dental Implantsmentioning
confidence: 99%